Dilemma of rural obstetrics. One community's solution. - Osmun, W. E. (College of Family Physicians of Canada, 1997)
PROBLEM BEING ADDRESSED: Increasing workload and concerns about physician exhaustion necessitated reorganizing the delivery of obstetric services on Manitoulin Island in Ontario. OBJECTIVE OF PROGRAM: To organize obstetrics in a remote rural community to provide safe, accessible care, improve working conditions for local physicians, and involve the local hospital and health care workers in the solution. MAIN COMPONENTS OF PROGRAM: A prenatal clinic for all obstetric care on the island was established. It was based at the local hospital and organized by a nurse-midwife. Local physicians rotated through the clinic and provided obstetric coverage on their on-call days. CONCLUSIONS: The clinic has helped improve working conditions for local physicians and maintain high-quality obstetric care in this remote area. Local women's initial resistance to the clinic seems to be disappearing with time. Ongoing chart audits reveal intervention rates similar to those found in other Canadian studies of rural obstetric care.